A comparison of maternal and newborn health services costs in Sindh Pakistan - Khowaja, Asif Raza (PLoS One, 2018)
Pakistani women suffer the highest rate of maternal mortality in South Asia. A lack of comprehensive knowledge about maternal and newborn health (MNH) services costs impedes policy decisions to maximize the benefit from existing, as well as emerging, MNH interventions in Pakistan. We compared MNH service costs at different levels of care. A cross-sectional survey was conducted during January to March 2016 as part of a large economic evaluation in Sindh, Pakistan. Health providers and facilities were selected from a sampling frame, inclusive of public and private sectors. This study utilized a broad perspective (i.e. costs to the health system and patients/families). The unit costs of MNH services were determined through a simultaneous allocation method in the public facilities; and patient billing department in the private facilities. Descriptive analysis was performed, and an analysis of variance (ANOVA) test was applied to compare overall mean costs both within and between health facilities. A total of 31 eligible health providers and facilities (n = 25 in private; n = 7 in public) were included in the final analysis. An ambulatory visit (AV) for routine antenatal care (ANC) costs $3.6 and $0.9 at secondary- and tertiary-level public facilities, respectively. In the private sector, the costs of an AV for ANC were slightly less ($2.8) at secondary-level and much higher ($6) at tertiary-level facilities compared to the public sector. Diagnostic test costs were much higher in private facilities. The average costs of inpatient admissions were $30.5 at general ward (GW), and $151 at the intensive care unit (ICU) in public facilities. In-patient admissions costs were lower such as $9.3 at GW and $36.5 at ICU in private facilities. Understanding cost is critical to guide decisions of resource allocation within the public sector; and risk mitigation for excessive OOP costs through third party payer for services in the private sector.